Gravid Uterus in a Neglected Incisional Hernia - Rohini R. Raut; Rangan Bhattacharya; Snehal G. Murde (Emerging Trends in Disease and Health Research Vol. 9, 2022)
Background: Incisional hernia is uncommon in pregnancy and is usually treated conservatively. Although there is no optimum strategy for management of incisional hernias in pregnant females, it is apparent that each case must be treated individually. Objective: To study management of a term pregnancy with incisional hernia. We report a case of incisional hernia in a term pregnancy of a third gravida, aged 30 years with previous two vaginal deliveries with overlying hyperpigmented lax skin patch. Incisional hernia developed as a result of a previous surgical history of open appendectomy 10 years prior, which had been complicated in the post-operative period, 22 days later, resulting to an emergency laparotomy due to intestinal obstruction. The incisional hernia was repaired with nonabsorbable sutures during the Caesarean section. Conclusion: Pregnancy with incisional hernia is a rare occurrence. Management is mainly conservative and individualised. Simultaneous hernia repair with caesarean section is safe and generally preferred.